Deradikalisasi Masjid Inklusi: Upaya Penghapusan Ideologi Radikal di Yogyakarta - Muryanti Muryanti; Tri Mulyani (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2019)
Radicalization has recently strengthened in Indonesia. The real act makes in burning and killing war. The violence war takes the results in casualties and damage. This paper talks the process of deradicalization in the cases of phenomenology radicalization in recent years. One of the activities on the issue is to restore the function of the mosque with various activities at 3 important mosques in Yogyakarta. The UIN Sunan Kalijaga Mosque as a Religious Laboratory in the development of da'wah, the Syuhada Mosque as an Educational and economic institution, and the Jogokaryan Mosque as a pesantren in prospering the environment. These 3 findings indicate the potential character of the inclusion mosque. This gave rise to empowerment activities in religious studies and economic education. the activities in the mosque's efforts to reduce radicalization based on religion.Radikalisasi atas nama agama akhir-akhir ini menguat di Indonesia. Wujud nyata dari hal tersebut adalah aksi teror. Hal ini menggunakan kekerasan yang berakibat korban jiwa dan kerusakan. Tulisan ini hendak mengkaji proses deradikalisasi dalam fenomena pada banyak kasus radikalisasi beberapa tahun ini. Salah satu aktivitas pada isu tersebut mengembalikan fungsi masjid dengan berbagai macam kegiatan pada 3 masjid penting di Yogyakarta. Masjid UIN Sunan Kalijaga sebagai Laboratorium Agama dalam pengembangan dakwah, Masjid Syuhada sebagai Lembaga Pendidikan dan ekonomi, dan Masjid Jogokaryan sebagai pesantren dalam memakmurkan lingkungan tersebut. 3 temuan ini menunjukan potensi karakter masjid inklusi. Hal ini memunculkan kegiatan pemberdayaan dalam kajian keagamaan dan Pendidikan ekonomi. Berbagai macam kegiatan dalam aktivitas masjid tersebut merupakan upaya meredam radikalisasi berbasiskan agama.